Variation in plastid genomes in the gynodioecious species Silene vulgaris - Krüger, Manuela; Abeyawardana, Oushadee A J; Juříček, Miloslav; Krüger, Claudia; Štorchová, Helena (BMC plant biology, 2019)
BACKGROUND: Gynodioecious species exist in two sexes - male-sterile females and hermaphrodites. Male sterility in higher plants often results from mitonuclear interaction between the CMS (cytoplasmic male sterility) gene(s) encoded by mitochondrial genome and by nuclear-encoded restorer genes. Mitochondrial and nuclear-encoded transcriptomes in females and hermaphrodites are intensively studied, but little is known about sex-specific gene expression in plastids. We have compared plastid transcriptomes between females and hermaphrodites in two haplotypes of a gynodioecious species Silene vulgaris with known CMS candidate genes. RESULTS: We generated complete plastid genome sequences from five haplotypes S. vulgaris including the haplotypes KRA and KOV, for which complete mitochondrial genome sequences were already published. We constructed a phylogenetic tree based on plastid sequences of S. vulgaris. Whereas lowland S. vulgaris haplotypes including KRA and KOV clustered together, the accessions from high European mountains diverged early in the phylogram. S. vulgaris belongs among Silene species with slowly evolving plastid genomes, but we still detected 212 substitutions and 112 indels between two accessions of this species. We estimated elevated Ka/Ks in the ndhF gene, which may reflect the adaptation of S. vulgaris to high altitudes, or relaxed selection. We compared depth of coverage and editing rates between female and hermaphrodite plastid transcriptomes and found no significant differences between the two sexes. We identified 51 unique C to U editing sites in the plastid genomes of S. vulgaris, 38 of them in protein coding regions, 2 in introns, and 11 in intergenic regions. The editing site in the psbZ gene was edited only in one of two plastid genomes under study. CONCLUSIONS: We revealed no significant differences between the sexes in plastid transcriptomes of two haplotypes of S. vulgaris. It suggests that gene expression of plastid genes is not affected by CMS in flower buds of S. vulgaris, although both sexes may still differ in plastid gene expression in specific tissues. We revealed the difference between the plastid transcriptomes of two S. vulgaris haplotypes in editing rate and in the coverage of several antisense transcripts. Our results document the variation in plastid genomes and transcriptomes in S. vulgaris.
Keywords: transkriptom; Genome, Plastid; Transcriptome; genom plastidový; Silene